A CMOS oversampled DAC with multi-bit semi-digital filtering and boosted subcarrier SNR for ADSL central office modems. - Lin, A.C.Y.
An oversampled digital-to-analog converter for use in ADSL central office modems has been integrated in 0.18-μm CMOS technology. The converter features a multi-bit semi-digital filter for reconstruction and a digital pre-emphasis filter that boosts the SNR of subcarriers affected by noise shaping and flattens the overall in-band magnitude response. A resampled impulse response is employed to simplify the implementation of the semi-digital filter. The combination of digital and semi-digital filtering allows the design to meet all ADSL performance requirements with only 180 current cells and a third-order analog low-pass reconstruction filter. When sampling at 200 MSample/s, the converter achieves 86-dB dynamic range for a 1.1-MHz bandwidth, with an average MTPR of 65 dB.
Keywords: 0.18 micron; 1.1 MHz; ADSL; CMOS technology; Asymmetric digital subscriber line; Boosted subcarrier SNR; Central office modems; Digital pre-emphasis filter; Impulse response; In-band magnitude response; Low-pass reconstruction filter; Multibit semi-digital filter; Noise shaping; Oversampled DAC; Oversampled digital-analog converter; Third-order analog filter